Preparation method of ceramic material for chopper
By using the principles of metal salt hydrolysis and Zeta potential opposite-attracting in the preparation of ZTA ceramic materials, uniform dispersion of zirconia is achieved, solving the problems of uneven dispersion and serious agglomeration of existing ceramic materials, and significantly improving the hardness and strength of the chopping knife.
Patent Information
- Application Number
- CN202411760388.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-03
AI Technical Summary
During the preparation process, existing ZTA ceramic materials have problems such as uneven dispersion, serious agglomeration and wide size distribution, resulting in insufficient hardness and strength of the chopper.
By adopting the principle of hydrolysis of metal salt and opposite-element absorption of Zeta potential, the pH value and temperature of aluminum salt hydrolysis can achieve uniform dispersion of zirconia and avoid agglomeration. The specific steps include heating a mixed solution of aluminum salt and organic solvent, hydrolyzing and adjusting the pH value, then mixing with a mixed solution of zirconium salt and organic solvent, performing a hydrolysis reaction and calcining, and finally producing a ceramic material.
Through this method, the zirconia and alumina particles are evenly dispersed in the prepared ceramic material, the particle size is small, the hardness and strength are significantly improved, the hardness of the chopper exceeds 1800MPa and the strength exceeds 750MPa.
Smart Images

Figure BDA0005167490600000071 
Figure BDA0005167490600000072 
Figure BDA0005167490600000081
Abstract
Description
Technical Field
[0001] The invention belongs to the field of semiconductor device packaging, and in particular relates to a method for preparing a ceramic material for a splitting knife. Background Art
[0002] In the production process of semiconductor integrated circuits, it is usually necessary to connect the semiconductor bare chip welding area with the I / O lead of the microelectronic package or the metal wiring welding area on the substrate with a metal filament (welding wire), so a splitter is needed for welding. Generally, the welding wire is passed through the wire hole of the splitter and welded by hot pressing bonding or ultrasonic bonding (that is, under the action of heating, pressure or friction, the atoms on the contact surface of the welding wire and the welding area reach the atomic attraction range and weld). At present, splitters usually use ZTA composite powder as raw material. High-performance ZTA composite powder is the prerequisite for preparing splitters with high strength and hardness.
[0003] The existing technology generally utilizes the mechanism of phase change toughening and particle dispersion. After compounding alumina and zirconium oxide in a certain proportion, ZTA composite powder with higher strength and hardness can be obtained. The preparation of high-performance ZTA composite powder is the prerequisite for obtaining a good ceramic body. The preparation methods of ZTA composite powder are mainly divided into solid phase method and liquid phase method. The solid phase method is to grind and mix alumina and zirconium oxide powder by high-energy ball milling. The powder particles prepared by this method are large, and zirconium oxide is unevenly dispersed in alumina. The liquid phase method is to co-precipitate zirconium salt and aluminum salt and then calcine to obtain ZTA composite powder. The powder particles prepared by this method are severely agglomerated and have a wide size distribution. Summary of the invention
[0004] In order to overcome the problems existing in the prior art, one of the objectives of the present invention is to provide a method for preparing a ceramic material.
[0005] A second object of the present invention is to provide a riving knife.
[0006] A third object of the present invention is to provide a method for preparing a splitting knife.
[0007] A fourth object of the present invention is to provide a method for preparing the above-mentioned ceramic material and / or the use of the above-mentioned splitting knife in manufacturing semiconductor products.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] A first aspect of the present invention provides a method for preparing a ceramic material, comprising the following steps:
[0010] S1: heating a mixed solution including an aluminum salt and an organic solvent to 25-45° C. to obtain a mixed solution A;
[0011] S2: dropping the hydrolyzate A into the mixed solution A to perform a hydrolysis reaction, adjusting the pH to 3-5, and obtaining a mixed solution B;
[0012] S3: mixing the mixed solution B with a mixed solution including a zirconium salt and an organic solvent, heating the mixture to 55-75° C., and then dropping the hydrolysis solution B to perform a hydrolysis reaction to obtain a mixed solution C;
[0013] S4: raising the temperature to remove the organic solvent to obtain a gel, which is then calcined to obtain the ceramic material.
[0014] In order to solve the problems of uneven dispersion, serious agglomeration and wide size distribution of traditional ZTA ceramic materials, the present invention combines the hydrolysis of metal salts with the principle of Zeta potential attraction, thereby preparing a ceramic material with good zirconium oxide dispersion and good uniformity of zirconium oxide and aluminum oxide particles. Specifically, in the early stage of aluminum salt hydrolysis (i.e., step S2), the pH value of the reaction system is adjusted to weak acidity. At this time, the surface of aluminum hydroxide produced by the reaction will adsorb H + In step S3, the hydrated zirconium oxide produced by the continued hydrolysis reaction is adsorbed around the aluminum hydroxide due to its negatively charged surface, forming a good dispersion system, thereby achieving uniform dispersion of zirconium oxide in the ceramic material and avoiding agglomeration of zirconium oxide particles.
[0015] In the present invention, the heating temperature in step S1 is 25-45°C, for example, it can be selected from 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C. Preferably, the heating temperature in step S1 is 30-40°C. In step S1, when the heating temperature is adjusted to the range of 25-45°C, the rate of aluminum salt hydrolysis can be controlled, so that the aluminum hydroxide generated for the first time is small and uniform; when the heating temperature is controlled within the range of 30-40°C, the aluminum salt hydrolysis reaction is more stable, which is more conducive to obtaining aluminum hydroxide particles with smaller and uniform particle size; if the heating temperature exceeds 45°C, the reaction temperature is too high, the reaction rate is too fast, and the size of the formed grains is uneven.
[0016] Preferably, the aluminum salt is selected from at least one of aluminum isopropoxide and aluminum n-propoxide.
[0017] Preferably, the zirconium salt is selected from at least one of zirconium isopropoxide and zirconium n-propoxide.
[0018] Preferably, the molar ratio of the aluminum salt to the zirconium salt is 1:(0.03-0.3), for example, it can be selected from 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1, 1:0.12, 1:0.14, 1:0.16, 1:0.18, 1:0.2, 1:0.22, 1:0.24, 1:0.26, 1:0.28, 1:0.3.
[0019] Preferably, the organic solvent is selected from at least one of isopropanol and n-propanol. When the aluminum salt is aluminum n-propoxide and the zirconium salt is zirconium n-propoxide, n-propanol is more conducive to the reaction; when the aluminum salt is aluminum isopropoxide and the zirconium salt is zirconium isopropoxide, isopropanol is more conducive to the reaction.
[0020] Preferably, in the mixed solution including aluminum salt and organic solvent, the molar ratio of aluminum salt to organic solvent is 1:(95-99), for example, it can be selected from 1:95, 1:96, 1:97, 1:98, 1:99. In the present invention, when the molar ratio of aluminum salt to organic solvent is within an appropriate range, it is beneficial to obtain ceramic powder with fine and uniformly dispersed zirconium oxide grains. In the present invention, the molar ratio of aluminum salt to organic solvent is preferably 1:(95-99). If the proportion of organic solvent is too high, the content of organic solvent in the reaction system is too large, and subsequent recovery is difficult, resulting in waste; if the proportion of organic solvent is too low, it will lead to gelation during the reaction process, and it is difficult to obtain particles of uniform size.
[0021] Preferably, in the mixed solution comprising zirconium salt and organic solvent, the molar ratio of zirconium salt to organic solvent is 1:(95-99), for example, can be selected from 1:95, 1:96, 1:97, 1:98, 1:99.
[0022] In the present invention, both the hydrolysis solution A and the hydrolysis solution B are mixed solutions of an organic solvent and water.
[0023] Preferably, the hydrolyzate A is a mixture of an organic solvent and water in a molar ratio of (0.1-0.3):1. For example, the molar ratio of the organic solvent to water can be selected from 0.1:1, 0.15:1, 0.2:1, 0.25:1, and 0.3:1.
[0024] Preferably, the molar ratio of the aluminum salt to the water in the hydrolyzed solution A is 1:(0.8-1.2). When the molar ratio of the aluminum salt to the water in the hydrolyzed solution A is within the above range, it is more conducive to the dispersion of zirconium and aluminum.
[0025] Preferably, the hydrolyzate B is a mixture of an organic solvent and water in a molar ratio of (0.1-0.3):1. For example, the molar ratio of the organic solvent to water can be selected from 0.1:1, 0.15:1, 0.2:1, 0.25:1, and 0.3:1.
[0026] Preferably, the molar ratio of the aluminum salt to the water in the hydrolyzed solution B is 1:(7-10). When the molar ratio of the aluminum salt to the water in the hydrolyzed solution A is within the above range, it is more conducive to the dispersion of zirconium and aluminum.
[0027] In the present invention, the water in the hydrolyzate A and the hydrolyzate B is diluted with an organic solvent, and the hydrolyzate A and the hydrolyzate B are added by dropwise addition, all in order to avoid excessive local saturation and make the reaction product agglomerate more seriously. The higher the multiple of water dilution with an organic solvent in the hydrolyzate A and the hydrolyzate B, the slower the dropwise addition speed, and the better the effect. However, considering the production efficiency, it also needs to be controlled within a certain range.
[0028] Preferably, step S2 comprises: dripping hydrolysis solution A into mixed solution A under stirring to carry out hydrolysis reaction, adjusting the pH to 3-5 with acid, and obtaining mixed solution B; the addition of hydrolysis solution A can hydrolyze part of the aluminum salt to generate aluminum hydroxide suspension.
[0029] Preferably, the step S2 is to adjust the pH to 3-5 using at least one acid selected from formic acid and acetic acid. The pH in step S2 is 3-5, for example, can be selected from 3, 4, 5. Under different pH conditions, there are differences in the charge on the surface of the reaction product; the purpose of adding acid is to adjust the pH value of the reaction system within a suitable range, adjust the Zeta potential of the reaction product, and make the aluminum hydroxide colloid positively charged, so that the aluminum oxide and zirconium oxide in the subsequent product can be evenly dispersed. The present invention controls the pH to 3-5, on the one hand, it can control the partial hydrolysis of the aluminum salt to generate an aluminum hydroxide suspension; on the other hand, the hydrolyzed hydrated zirconium oxide particles can be adsorbed onto the aluminum hydroxide suspension particles to achieve the purpose of dispersing zirconium oxide. When using acid to adjust the pH value, it is necessary to consider that the acid is liquid and the water content is as little as possible to avoid hydrolysis reaction when adding acid. Formic acid and acetic acid are both easy to obtain high-purity acid solutions, which are suitable for adjusting the pH value, while anhydrous nitric acid is easy to decompose and cannot be used. Citric acid is solid and is not applicable. If too much acid is used, the pH value will be too low and the subsequent reaction will be difficult to proceed. If too little acid is used, the pH value will be high, the surface of the reaction product will have less positive charge, and the mixing effect of zirconium oxide and aluminum oxide will be poor.
[0030] In the present invention, the temperature after heating in step S3 is 55-75°C, for example, it can be selected from 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C; preferably, the heating temperature of step S3 is 60-70°C. In step S3, the temperature is raised to 55-75°C, which is conducive to improving the reaction rate; the higher the temperature, the more conducive to improving the reaction rate, and the smaller the particle size of the obtained reaction product, but too high a temperature will cause the reaction product particles to migrate too fast and the electrostatic adsorption effect will be weakened.
[0031] Preferably, the hydrolysis reaction time in step S3 is greater than 2 h; further preferably, the hydrolysis reaction time in step S3 is 2 h to 24 h, for example, can be selected from 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h.
[0032] Preferably, the heating temperature in step S4 is 100-120°C, for example, it can be selected from 100°C, 101°C, 102°C, 103°C, 104°C, 105°C, 106°C, 107°C, 108°C, 109°C, 110°C, 111°C, 112°C, 113°C, 114°C, 115°C, 116°C, 117°C, 118°C, 119°C, 120°C; further preferably, the heating temperature in step S4 is 105-115°C. In step S4, the temperature is raised to 100-120°C in order to recover the organic solvent and dry the reaction product into a gel before the next step of calcination. If the heating temperature is too low, the amount of recovered organic solvent decreases, resulting in a waste of organic solvent; if the temperature is too high, the heating cost is increased, resulting in a waste of energy. The organic solvent used in the present invention can be completely recovered at 100-120°C.
[0033] Preferably, the calcination temperature in step S4 is 1000-1100°C, for example, can be selected from 1000°C, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C.
[0034] Preferably, the calcination holding time in step S4 is 1 to 3 hours, for example, can be selected from 1 hour, 1.5 hours, 2 hours, 2.5 hours, and 3 hours.
[0035] The second aspect of the present invention provides a splitting knife, which includes a splitting knife body, a welding nozzle and a wire through hole, wherein the wire through hole extends along the longitudinal axis direction of the splitting knife body to the inner chamfer of the welding nozzle, and the splitting knife is made of raw materials including the ceramic material prepared by the preparation method described in the first aspect of the present invention.
[0036] The third aspect of the present invention provides a method for preparing the splitting knife according to the second aspect of the present invention, comprising the following steps:
[0037] The ceramic material prepared by the preparation method described in the first aspect of the present invention is mixed with a dispersant and a solvent and ground to obtain a ceramic slurry;
[0038] The ceramic slurry is dried to form a shape and then sintered.
[0039] Preferably, the dispersant comprises ammonium polyacrylate.
[0040] Preferably, the grinding is performed by ball milling.
[0041] Preferably, the ball milling time is 4 to 6 hours, for example, can be selected from 4 hours, 4.5 hours, 5 hours, 5.5 hours, and 6 hours.
[0042] Preferably, the drying temperature is 100-120°C, for example, can be selected from 100°C, 101°C, 102°C, 103°C, 104°C, 105°C, 106°C, 107°C, 108°C, 109°C, 110°C, 111°C, 112°C, 113°C, 114°C, 115°C, 116°C, 117°C, 118°C, 119°C, and 120°C.
[0043] Preferably, the sintering temperature is 1400-1600°C, for example, can be selected from 1400°C, 1450°C, 1500°C, 1550°C, 1600°C.
[0044] Preferably, the sintering holding time is 1 to 3 hours, for example, can be selected from 1 hour, 2 hours, and 3 hours.
[0045] The fourth aspect of the present invention provides a method for preparing the ceramic material according to the first aspect of the present invention and / or use of the wedge according to the second aspect of the present invention in manufacturing semiconductor products.
[0046] The beneficial effects of the present invention are as follows: the preparation method of the present invention can refine the grain size of aluminum oxide and zirconium oxide by controlling the temperature in three stages and adjusting the pH during the hydrolysis of aluminum salt, so that zirconium oxide is evenly distributed in aluminum oxide and agglomeration of zirconium oxide is avoided.
[0047] The zirconium oxide grains and aluminum oxide grains in the splitting cutter of the present invention are both small in size. The zirconium oxide grain size is less than 0.5 μm, and the CV value is not more than 16%. The aluminum oxide grain size is less than 1 μm, and the CV value is not more than 21%. The zirconium oxide is evenly dispersed in the aluminum oxide without agglomeration, thereby improving the hardness and strength of the splitting cutter, so that the hardness of the splitting cutter is greater than 1800 MPa, and the strength is greater than 750 MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a cross-sectional morphology test diagram of the ceramic splitting knife in Example 1.
[0049] Figure 2 This is a cross-sectional morphology test diagram of the ceramic splitting knife in Comparative Example 4. DETAILED DESCRIPTION
[0050] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0051] The ceramic splitting knives prepared in Examples 1 to 7 of the present invention and Comparative Examples 1 to 5 are all cylindrical structures. The structure of the ceramic splitting knives includes a splitting knife body, a welding nozzle and a wire through hole. The wire through hole extends along the longitudinal axis direction of the splitting knife body to the inner chamfer of the welding nozzle (the specific structure of the ceramic splitting knife can be referred to CN108610028A).
[0052] Example 1
[0053] This example provides a method for preparing a ceramic splitter, which comprises the following steps:
[0054] 1. Stir 1 mol of aluminum n-propoxide and 99 mol of n-propanol to obtain a mixed solution A, and keep the oil bath at a constant temperature of 35°C, that is, the temperature A is 35°C;
[0055] 2. While maintaining stirring, slowly dropwise add hydrolyzate A prepared by mixing 0.25 mol of n-propanol and 1 mol of deionized water into mixed solution A, and then adjust the pH value of the system to 4 with formic acid to obtain mixed solution B.
[0056] 3. Add 0.14 mol of zirconium n-propoxide and 13.86 mol of n-propanol to the mixed solution B, raise the oil bath temperature to 65°C (i.e., temperature B is 65°C) and stir well. While keeping stirring, slowly dropwise add the hydrolyzate B prepared by mixing 2.03 mol of n-propanol and 8.12 mol of deionized water to react. After the reaction, stir for 2 hours to obtain a mixed solution C.
[0057] 4. Raise the oil bath temperature to 105°C to evaporate and recover the alcohol in the mixed solution C, and obtain a gel in which zirconium and aluminum are evenly dispersed.
[0058] 5. The obtained gel was placed in a muffle furnace, calcined at 1000°C, and kept warm for 1.5 hours to obtain a mixture of zirconium oxide and aluminum oxide;
[0059] 6. Put the mixture into a ball mill, add deionized water and dispersant ammonium polyacrylate, ball mill for 4 hours, dry and shape at 110°C to obtain a molded body.
[0060] 7. The formed body is sintered at 1450° C. in an air atmosphere, kept at this temperature for 2 hours, and then cut, grind and polish to obtain the ceramic splitting tool in this example.
[0061] Embodiment 2-3
[0062] The only difference between the preparation methods of the ceramic splitting knives in Examples 2 to 3 and Example 1 is that the temperature A in step 1 is different, as shown in Table 1 below.
[0063] Embodiment 4-5
[0064] The only difference between the preparation methods of the ceramic splitting knives in Examples 4 to 5 and Example 1 is that the temperature B in step 3 is different, as shown in Table 1 below.
[0065] Embodiment 6-7
[0066] The only difference between the preparation methods of the ceramic splitting knives in Examples 6 to 7 and Example 1 is that the pH values adjusted in step 2 are different. The specific pH values are shown in Table 1 below.
[0067] Comparative Example 1
[0068] The preparation method of the ceramic splitting knife in this example is different from that in Example 1 only in that the temperature A in step 1 of this example is different, as shown in Table 1 below.
[0069] Comparative Examples 2-3
[0070] The only difference between the preparation methods of the ceramic splitting knives in Comparative Examples 2 to 3 and Example 1 is that the temperature B in step 3 is different, as shown in Table 1 below.
[0071] Comparative Example 4
[0072] The preparation method of the ceramic splitting knife in this example is different from that in Example 1 only in that formic acid is not used to adjust the pH value in step 2 of this example.
[0073] Comparative Example 5
[0074] The preparation method of the ceramic splitting knife in this example is different from that in Example 1 only in that in step 2 of this example, hydrolysis solution A is not added, but formic acid is directly added to adjust the pH value.
[0075] Table 1 Preparation process parameters in Examples 1 to 7 and Comparative Examples 1 to 5
[0076] Serial number Temperature A / ℃ pH Temperature B / ℃ Example 1 35 4 65 Example 2 25 4 65 Example 3 45 4 65 Example 4 35 4 55 Example 5 35 4 75 Example 6 35 3 65 Example 7 35 5 65 Comparative Example 1 50 4 65 Comparative Example 2 35 4 50 Comparative Example 3 35 4 80 Comparative Example 4 35 7.5 65 Comparative Example 5 35 4 65
[0077] Performance Test:
[0078] The hardness, zirconia grain size, alumina grain size and three-point bending strength of the ceramic splitters prepared in Examples 1 to 7 and Comparative Examples 1 to 5 were tested respectively according to the test methods described in Table 2 below. The specific test results are shown in Table 3 below.
[0079] Table 2 Test methods and compliance requirements
[0080]
[0081] Table 3 Performance test data of ceramic splitter
[0082]
[0083]
[0084] As can be seen from Table 3, the preparation method of the ceramic splitting knife in Examples 1 to 7 of the present invention can achieve the refinement of the zirconium oxide grains and aluminum oxide grains in the ceramic splitting knife by controlling the temperature A at 25 to 45°C, the temperature B at 55 to 75°C, and the pH of the mixed solution B at 3 to 5, and make the zirconium oxide evenly dispersed in the aluminum oxide (the smaller the average value of the zirconium oxide and aluminum oxide grain sizes, the better the dispersion uniformity of the zirconium oxide), avoid the agglomeration of zirconium oxide, and thus improve the hardness and strength of the ceramic splitting knife, so that the hardness of the ceramic splitting knife is greater than 1800MPa and the strength is greater than 800MPa.
[0085] The cross-sectional morphology of the ceramic splitters in Example 1 and Comparative Example 4 was tested by scanning electron microscopy. The specific test results are as follows: Figure 1 and Figure 2 As shown, Figure 1 and Figure 2 The whiter particles are zirconium oxide particles, and the grayer particles are aluminum oxide particles. Figure 1 and Figure 2 It can be seen that the size difference between the zirconium oxide particles and the aluminum oxide particles in the ceramic splitter of Example 1 is small, and the zirconium oxide grains are evenly distributed without agglomeration. This test result is consistent with the test data in Table 3. However, the size difference between the zirconium oxide particles and the aluminum oxide particles in the ceramic splitter of Comparative Example 4 is large, and the zirconium oxide particles are agglomerated.
[0086] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A method for preparing a ceramic material, characterized in that: The following steps are involved: S1: heating a mixed solution including an aluminum salt and an organic solvent to 25-45° C. to obtain a mixed solution A; S2: dropping the hydrolyzate A into the mixed solution A to perform a hydrolysis reaction, adjusting the pH to 3-5, and obtaining a mixed solution B; S3: mixing the mixed solution B with a mixed solution including a zirconium salt and an organic solvent, heating the mixture to 55-75° C., and then dropping the hydrolysis solution B to perform a hydrolysis reaction to obtain a mixed solution C; S4: raising the temperature to remove the organic solvent to obtain a gel, which is then calcined to obtain the ceramic material.
2. The method for preparing the ceramic material according to claim 1, characterized in that: The aluminum salt is selected from at least one of aluminum isopropoxide and aluminum n-propoxide; And / or, the zirconium salt is selected from at least one of zirconium isopropoxide and zirconium n-propoxide; And / or, the organic solvent is selected from at least one of isopropanol and n-propanol.
3. The method for preparing the ceramic material according to claim 1, characterized in that: In the mixed solution comprising aluminum salt and organic solvent, the molar ratio of aluminum salt to organic solvent is 1:(95-99); And / or, in the mixed solution comprising zirconium salt and organic solvent, the molar ratio of zirconium salt to organic solvent is 1:(95-99); And / or, the hydrolyzate A is a mixture of an organic solvent and water in a molar ratio of (0.1-0.3):1; And / or, the hydrolysis solution B is a mixture of an organic solvent and water in a molar ratio of (0.1-0.3):
1.
4. The method for preparing the ceramic material according to claim 1, characterized in that: The step S2 is to adjust the pH to 3-5 using at least one acid selected from formic acid and acetic acid.
5. The method for preparing the ceramic material according to claim 1, characterized in that: The hydrolysis reaction time in step S3 is greater than 2 hours.
6. The method for preparing the ceramic material according to claim 1, characterized in that: The heating temperature in step S4 is 100-120°C; And / or, the calcination temperature in step S4 is 1000-1100° C.; And / or, the calcination holding time in step S4 is 1 to 3 hours.
7. A splitting knife, comprising a splitting knife body, a welding nozzle and a wire through hole, wherein the wire through hole extends along the longitudinal axis of the splitting knife body to the inner chamfer of the welding nozzle, characterized in that: The splitting knife is made of raw materials including ceramic materials prepared by the preparation method according to any one of claims 1 to 6.
8. The method for preparing the splitting knife according to claim 7, characterized in that: The following steps are involved: The ceramic material prepared by the preparation method according to any one of claims 1 to 6 is mixed with a dispersant and a solvent and ground to obtain a ceramic slurry; The ceramic slurry is dried to form a shape and then sintered.
9. The method for preparing a splitting knife according to claim 8, characterized in that: The sintering temperature is 1400-1600°C; And / or, the sintering holding time is 1 to 3 hours.
10. Use of the method for preparing the ceramic material according to any one of claims 1 to 6 and / or the splitter according to claim 7 in manufacturing semiconductor products.
Citation Information
Patent Citations
Ceramic capillary
CN108610028A
Process for production of composite of metal oxides, composite powders of metal oxides and ceramic materials
CN1049485A
Preparation method of nano-yttrium-stabilized zirconia-alumina composite powder
CN109704731A
Composite zirconium oxide powder for dentistry and preparation method thereof
CN114044670A
Zirconia-alumina composite powder and process for preparation thereof
TW201217302A
Cited By
ZTA ceramic powder, ceramic substrate and preparation method thereof
CN121318399A